65.1k views
4 votes
Simplify, using the distributive property and then combining like terms. 4(2x+y)-3(x+y)

2 Answers

2 votes

Answer:

5x + y

Explanation:

4(2x + y) - 3(x + y) = 4*2x + 4y - 3x - 3y = 8x - 3x + 4y - 3y = 5x + y

User FelixRabe
by
6.6k points
3 votes

Hello!

Answer:

:
\boxed{ \bf The~answer~is~5x~+~y}

___________________________________

Explanation:

4(2x+y)-3(x+y)

Multiply everything inside the brackets by the number outside.

= 8x + 4y - 3x - 3y

Next, combine like terms.

= 8x - 3x + 4y - 3y

= 5x + y

User GnanaJeyam
by
5.5k points